Inter-Relationship between Economic Development and Human Development- Analytical Study of selected Arab Countries - Ahmad Omar, Dina (Utopía y Praxis Latinoamericana, 2020)
ABSTRACTThe research aims to study the inter-relationship between economic development and human development indicators for a selected countries (Jordan, Egypt, Kingdom of Saudi Arabia and Bahrain) by using two stage least Square Test. The results of the test showed that there is a causality relation between the economic development and human development. We found economic development has clear effect on human development indicators in the selected Arab countries.